Community Empowerment in Efforts to Prevent Stunting Based on the Health Belief Model in Milangasri Village, Panekan District, Magetan Regency - Suharto, Agung; Santosa, Budi Joko; Setiyani, Astuti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
ABSTRACT Introduction, stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their body length or height being below standard. The number of stunted toddlers in Milangasri Village, Panekan District, Magetan Regency in 2022 will be 4 (four) toddlers. Milangasri Village, which is part of the Panekan sub-district, contributes around 4% of all malnourished children under five in Magetan Regency. Coverage of healthy living behavior at household level in Panekan sub-district is around 46%, this achievement is smaller than the national standard of 60%. Efforts to overcome stunting directly touch aspects of knowledge, attitudes, behavior and skills of families and communities through integrated community service activities and are carried out starting from monitoring from pregnancy until the child is at least two years old. Method, community service by providing education about stunting prevention using pre-test-posttest. Location of community service activities in Milangasri Village, Panekan District, Magetan Regency. Results. Characteristics of community service participants, most of whom are 31-35 years old, 38%, most of the participants' education is secondary (high school or equivalent) as much as 57% and the occupation of most of the community service participants is housewives, 35%. There has been an increase in posyandu prevention knowledge regarding stunting prevention based on the health belief model. Conclusion: There has been an increase in posyandu prevention knowledge regarding stunting prevention based on the health belief model.